Acute and chronic effects of acupuncture on radial artery: A randomized double blind study in migraine - Pierre Boutouyrie; Robert Corvisier; Kim-Than Ong; Claire Vulser; Catherine Lassalle; Michel Azizi; Brigitte Laloux; Stéphane Laurent (Artery Research, 2010)
Background: Acupuncture is an accepted treatment for migraine. Palpation of the radial pulses is one of the most important techniques in traditional Chinese medicine both for diagnosis and monitoring of treatment efficacy. The objective of the present study was to investigate the acute and chronic effects of acupuncture on the radial artery of patients suffering from severe migraine. Methods: A double-blind parallel group study was conducted in 31 patients never exposed to acupuncture and randomized in two groups : real acupuncture versus sham acupuncture, applied 3 times at one month interval. At baseline and after 2 months, radial artery diameter was measured with a high resolution echotracking system before and during a 20 min’s acupuncture session. Migraine severity was assessed by self administrated questionnaires and visual analogic scale for pain at each visit. Patients and investigators (not acupuncture physician) were blinded as to the treatment allocation. Results: During the first session, radial artery diameter significantly increased after real acupuncture, (+3.1% IQR [−3.2–8.5], P = 0.03 vs 0.9% IQR [−5.3–5.8], P = NS), and remained significantly higher after the two months treatment course 5.2% IQR [−3.9–14] vs. −4.4% IQR [−10.0–3.5], respectively; P < 0.01). Patients with the most severe pain at baseline were less prone to dilate their arteries during follow-up (P < 0.05). A larger arterial vasodilatation after real acupuncture was observed for any given level of pain intensity (P < 0.01). Conclusion: an acupuncture-induced vasodilatation was observed at the site of the radial artery in patients suffering from severe migraine and naïve to acupuncture. The vasodilatation was maintained after chronic treatment. Condensed abstract: This double-blind randomized, controlled trial aimed at showing the acute and chronic vasodilatory response to acupuncture in migrainers naïve to acupuncture. We show that real acupuncture is accompanied by acute and chronic vasodilation of the radial artery, the chronic vasodilation is inversely related to the level of pain at baseline.